Μ‐Opioid Receptor Attenuates Aβ Oligomers‐Induced Neurotoxicity Through mTOR Signaling. (21st August 2014) - Wang, Yan; Wang, Yan‐Xia; Liu, Ting; Law, Ping‐Yee; Loh, Horace H.; Qiu, Yu; Chen, Hong‐Zhuan
Summary Aims μ‐opioid receptor (OPRM1) exerts many functions such as antinociception, neuroprotection, and hippocampal plasticity. A body of evidence has shown that OPRM1 activation could stimulate downstream effectors of mechanistic/mammalian target of rapamycin (mTOR). However, it is not clear whether OPRM1 protects neurons against β‐amyloid peptide (Aβ) neurotoxicity through mTOR signaling. Methods The effects of OPRM1 activation on Aβ oligomers‐induced neurotoxicity were assessed by cell viability and neurite outgrowth assay in primary cultured cortical neurons. The activities of mTOR, protein kinase B (Akt) and p70 ribosomal S6 kinase (p70 S6k) upon OPRM1 activation by morphine were measured by immunoblotting their phosphorylation status. Results Morphine dose‐dependently attenuated Aβ oligomers‐induced neurotoxicity. Aβ oligomers downregulated mTOR signaling. Morphine significantly rescued mTOR signaling by reversal of Aβ oligomers' effect on mTOR and its upstream signaling molecule Akt, as well as its downstream molecule p70 S6k. Moreover, the neuroprotective effect of morphine could be reversed by OPRM1 selective antagonist and phosphatidylinositol 3‐kinases (PI3K), Akt and mTOR inhibitors. Furthermore, endogenous opioids–enkaphalins also attenuated Aβ oligomers‐induced neurotoxicity. Conclusions Our findings demonstrated OPRM1 activation attenuated Aβ oligomers‐induced neurotoxicity through mTOR signaling. It may provide new insight into the pathological process and useful strategy for therapeutic interventions against Aβ neurotoxicity.